Dual Energy X-Ray Absorptiometry Analysis of Broiler Breeder Eggs for Prediction of Egg Components and Evaluation of Egg Shell Quality - England, J.A.; Salas, C.; Ekmay, R.D.; Coon , C.N. (International Journal of Poultry Science, 2012)
Most methods for evaluating shell quality and egg components are destructive and time consuming. Four trials were conducted to investigate the use of Dual Energy X-ray Absorptiometry (DXA) as a fast and non-destructive method for evaluating shell quality and measuring the components of broiler breeder eggs. In Trial 1, 180 eggs were scanned with a GE Lunar Prodigy DXA. The eggs were also evaluated by traditional methods that required breaking the eggs for shell quality evaluation and egg components (shell, albumen and yolk) weighed. Values obtained from the DXA scans were subjected to stepwise regression analysis to develop prediction equations. Prediction equations were developed for the weight of egg components (egg, yolk, albumen and shell) and parameters of shell quality (shell weight, thickness and calcium content). In Trial 1, the r2 values for the prediction equations using DXA values were 0.9961, 0.9692, 0.9843, 0.6891, 0.8499 and 0.5738 for the total egg weight, shell weight, shell calcium content, shell thickness, albumen weight and yolk weight, respectively (P>F, <0.0001). In Trial 2, 180 eggs were scanned to validate the prediction equations developed in Trial 1. Results from Trial 2 indicate that the prediction equations using DXA values are an effective method for predicting total egg weight, shell weight, shell calcium content, shell thickness, albumen weight and yolk weight (P>F, <0.0001). In Trial 3, 250 hatching eggs were scanned to determine the affect of scanning on hatchability. DXA scanning had no negative effect on hatchability, hatch chick weight or hatch residue breakout. In Trial 4, the specific gravity of 400 hatching eggs was determined by flotation in salt solutions. The eggs were then scanned with the DXA and values obtained from these scans were used to calculate SWUSA and shell:egg weight ratios. The SWUSA and shell:egg weight ratios determined by DXA scan were useful in predicting eggshell quality and correlated closely with actual specific gravity values (r = 0.7849, p<0.0001). A SWUSA of 75.1 and specific gravity of 1.081 corresponded to a shell:egg weight ratio of 0.0895 and 0.0924, respectively. Following the evaluation of egg shell quality by DXA and specific gravity, the 400 eggs were incubated to determine hatchability. Shell:egg weight ratios less than 0.0895 significantly increased the number of early dead (p = 0.02) during the hatchability study. By defining the scan area it is possible to scan and analyze 140 eggs per hour for all egg components and shell quality. DXA offers the primary breeder or researcher a method for selecting individual hens, based on egg component and shell quality profiles, which may improve the performance of the progeny.